UMPSA hosts Community Rehabilitation Programme Engagement Session - Nor Salwana, Mohammad Idris (UMPSA, 2024)
PEKAN, 26 June 2024 - The Disability Services Unit of Universiti Malaysia Pahang Al-Sultan Abdullah (OkUMPSA) in collaboration with the Pahang State Department of Social Welfare (JKM) organised a Pahang State Level Community Rehabilitation Programme (PPDK) Engagement Session at the Main Lecture Hall, Centre for Modern Languages (CML), UMPSA Pekan yesterday.